Cover Picture: (Isr. J. Chem. 7‐8/2021). Issue 7 (8th August 2021) - Unknown
Abstract : The Cover art presents a collage of graphical display items selected from various articles constituting this special issue honoring Barry M. Trost′s 80th birthday. Articles submitted for this occasion can be found in the Special Collection on the Organometallic Door to Synthesis.